Diagnostic Profile of Inferential Reading Ability across Four Indicators among Fifth Graders in Bandung Elementary Schools - Indra Suhendra; Wahyu Sopandi; Isah Cahyani; Cepi Riyana (Sakura Digital Nusantara, 2026)
Purpose: This study aimed to construct a diagnostic profile of inferential reading ability across four indicators anaphoric resolution, background knowledge activation, predictive reasoning, and retrospective synthesis among fifth-grade students in Bandung elementary schools, addressing the limited availability of dimension-specific empirical data on inferential reading performance at the primary level. Methods: A descriptive survey was conducted with 84 fifth-grade students from three public elementary schools in Bandung, who completed an inferential reading test structured around the four indicators. A broader cohort of 185 students from the same schools responded to a perception questionnaire, while 35 teachers completed a questionnaire on instructional practices. Semi-structured interviews were also conducted with three classroom teachers and three students. Descriptive statistics, frequency distributions, cross-school comparisons, and thematic analysis were employed. Findings: The overall mean score was 45.83 (SD = 15.94), with the majority of students performing below expected levels. Retrospective synthesis recorded the lowest mean (M = 39.06, 84.5% in the lowest category), followed by predictive reasoning and background knowledge activation (78.6% each). Anaphoric resolution, although the highest (M = 54.69), still left more than half of the students below the expected threshold. Comparable patterns were observed across the three schools. Research Implications: The findings indicate that inferential reading competence requires more systematic instructional attention, particularly in retrospective synthesis and predictive reasoning. The four-indicator diagnostic framework offers educators a tool for pinpointing dimension-specific weaknesses and provides researchers a baseline for future intervention studies. Originality: This study contributes an empirically grounded diagnostic profile of inferential reading ability across four discrete indicators at the elementary level, integrating objective test data with teacher and student perceptual evidence within a single analytical framework.